Comparative Analysis of Gender Representation in English Textbooks for Indonesian Junior High School Students - Siti Nurul Jameaah; Iwan Setiawan; Istanti Hermagustiana (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2024)
This study compares gender representations in three different English textbooks from three publishers used by Indonesian Junior High School students (the Indonesian government, an Indonesian private publisher, and an International publisher). Under Critical Discourse Analysis (CDA) and Systemic Functional Linguistics (SFL), the study specifically investigated males’ and females’ representations and the typical activities associated with both genders. Overall, the results showed that males dominated all the textbooks, visually and textually. Besides that, the analysis revealed that females still have lower representations, less variation in occupations, and feminine specialization in doing the household chores in two textbooks. However, positive representations and stereotypes also appear in the textbooks, such as neutral generic constructions and typical activities by both genders.